Decoding chronic pain: the glutamate-GABA tug of war in the cerebral cortex - Huang, Dan; Dong, Yu-Ting; He, Liu-Xuan; Zhou, Rui-Zhu; Zhou, Jian-Xiong; Yang, Sha; Yu, Shu-Guang (Frontiers in Molecular Neuroscience, 2025)
A sustained imbalance between excitatory and inhibitory mechanisms within the glutamatergic and GABAergic systems of the cerebral cortex, induced by noxious stimuli, is a fundamental characteristic in the development and maintenance of chronic pain. This review provides a comprehensive summary of the roles and interaction of glutamatergic and GABAergic systems in the processing of chronic pain signals. Specifically, we present a systematic summary of the processing patterns of the cerebral cortex in the cross-modular integration and output of chronic pain information, according to four aspects, molecular, cellular, neural network and behavioral cognition. These patterns consist of neuronal responses in individual cortical regions, neuron-astrocyte interactions, sharing and cascading of inter-cortical signals, and downward cortical modulation. Furthermore, a number of potential therapeutic approaches to the chronic pain are discussed from the pain management perspective.